Twelve tips for medical students to facilitate a Photovoice project. (2nd October 2016) - Jaiswal, Deep; To, Matthew J.; Hunter, Heather; Lane, Ciaran; States, Cinera; Cameron, Brittany; Clarke, Suzanne Kathleen; Cox, Catherine; MacLeod, Anna
Abstract: Participatory action projects, such as Photovoice, can provide medical trainees with a unique opportunity for community engagement. Through Photovoice, participants with lived experience engage in dialog and capture photographs of community issues. Participants subsequently develop narratives that accompany photos to raise awareness about community needs. In this paper, we describe twelve tips to develop a Photovoice project and discuss how medical students can engage communities through a participatory action lens. Such an approach not only serves as a method for medical students to learn about social determinants of health through the perspective of lived experience, but also has the capacity of building advocacy and community collaboration skills. Through providing a voice to marginalized individuals using Photovoice, medical students can partner with communities to work toward social change. Photovoice participants also benefit from the project as it provides them with a platform to highlight strengths and weaknesses in their community.